2005
DOI: 10.1007/bf03035151
|View full text |Cite
|
Sign up to set email alerts
|

Cinétique et caractérisation du phénomène “apoptosis-like” induit au cours de la congélation des spermatozoïdes bovins

Abstract: RESUMELa congdlation des spermatozo'ides ejacul6s bovins induit une mortalitd cellulaire elevee. Au cours d'une etude pr~liminaire, nous avions decrit qu'elle s'accompagne d'un processus oO apparaissent plusieurs caracteristiques pr~coces de I'apoptose : i) diminution du potentiel de membrane mitochondrial (A~=), ii) activation des caspases, iii) augmentation de la permeabilitd membranaire, sans apparition des caracteristiques tardives : iv) pas de fragmentation de I'ADN.Pour pr~ciser ce mecanisme, nous avons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, phosphatidylserine externalization was expressed with a higher frequency in the purified fractions of spermatozoa with low motility (Barroso et al, 2000(Barroso et al, , 2006Weng et al, 2002). However, others did not find any correlation between sperm apoptosis and semen quality (Ricci et al, 2002;Lachaud et al, 2004;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, phosphatidylserine externalization was expressed with a higher frequency in the purified fractions of spermatozoa with low motility (Barroso et al, 2000(Barroso et al, , 2006Weng et al, 2002). However, others did not find any correlation between sperm apoptosis and semen quality (Ricci et al, 2002;Lachaud et al, 2004;Martin et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The presence of translocated phosphatidylserine in human ejaculated spermatozoa has also been studied. In semen, increased rates of externalized phosphatidylserine were associated with decreased sperm motility (Oosterhuis et al, 2000;Shen et al, 2002;Weng et al, 2002;Barroso et al, 2006;Varum et al, 2007), normal morphology (Shen et al, 2002) or concentration (Ricci et al, 2002), whereas no association to abnormal semen parameters was found by others (Barroso et al, 2000;Ricci et al, 2002;Lachaud et al, 2004;Martin et al, 2005). These contradictory results mostly derived from the criteria used for group classification, which were based on individual semen parameters without taking into consideration all of them together.…”
Section: Introductionmentioning
confidence: 95%